Perceived doctor-patient relationship and satisfaction with general practitioner care in older persons in residential homes. (3rd April 2018) - de Waard, Claudia S.; Poot, Antonius J.; den Elzen, Wendy P. J.; Wind, Annet W.; Caljouw, Monique A. A.; Gussekloo, Jacobijn
Abstract: Objective: Understanding patient satisfaction from the perspective of older adults is important to improve quality of their care. Since patient and care variables which can be influenced are of specific interest, this study examines the relation between patient satisfaction and the perceived doctor-patient relationship in older persons and their general practitioners (GPs). Design: Cross-sectional survey. Subjects and setting: Older persons ( n = 653, median age 87 years; 69.4% female) living in 41 residential homes. Main outcome measures: Patient satisfaction (report mark) and perceived doctor-patient relationship (Leiden Perioperative care Patient Satisfaction questionnaire); relationships were examined by comparing medians and use of regression models. Results: The median satisfaction score was 8 (interquartile range 7.5–9; range 0–10) and doctor-patient relationship 65 (interquartile range 63–65; range 13–65). Higher satisfaction scores were related to higher scores on doctor-patient relationship (Jonckheere Terpstra test, p for trend <.001) independent of gender, age, duration of stay in the residential home, functional and clinical characteristics. Adjusted for these characteristics, per additional point for doctor-patient relationship, satisfaction increased with 0.103 points (β = 0.103, 95% CI 0.092–0.114; p < .001). In those with a 'low' doctor-patient relationship rating, the percentage awarding 'sufficient or good' to their GP for 'understanding about the personal situation' was 12%, 'receiving attention as an individual' 22%, treating the patient kindly 78%, and being polite 94%. Conclusion: In older persons, perceived doctor-patient relationship and patient satisfaction are related, irrespective of patient characteristics. GPs may improve patient satisfaction by focusing more on the affective aspects of the doctor-patient relationship. Key Points: Examination of the perceived doctor-patient relationship as a variable might better accommodate patients' expectations and improve satisfaction with the provided primary care.